Prevalence of human papillomavirus in tissue lesions of oral lichen planus patients - Reza Zare; Narges Ghazi; Farnaz Mohajertehran; Narges Asfiaee; Pendar Argani; Negar Khodaeni; Salehe Akhondian (Reviews in Clinical Medicine, 2022)
Introduction:Oral lichen planus treatment offers favorable clinical results over time due to its widespread prevalence. However, to date, there is still no theoretical agreement on the cause of this disease. Therefore, the present study aimed to investigate the frequency of human papillomavirus (HPV) DNA in oral lichen planus (OLP) tissue samples by the polymerase chain reaction (PCR) method.Methods:This retrospective study was carried out from 1387 to 1398 on 40 OLP samples (24non-erosive-atrophic and 16 erosive-atrophic forms) in the Oral Pathology Department of Mashhad Dental School. Polymerase chain reaction (PCR) was undertaken to identify HPV-DNA. Subsequently, the samples for HPV-DNA underwent PCR analysis again with the specific primers. The data were analyzed statistically by chi-square and independent t-test test regarding the significance levelof lower than 0.05.Results: The population consisted of 29 women (72.5%) and 11 men (27.5%) with an average age of 49.48± 2.78 years. Human papillomavirus DNA in none of the studied samples (in none of the groups) was detected by PCR. Gender distribution in the studied groups was not significantly different from each other, as the groups did not differ significantly in average age.Conclusion: No HPV-positive samples were observed in oral lichen planus samples based on the recent findings in the current study of the Iranian population. Nevertheless, the patients› demographic data were not meaningfully associated. More sample sizes with a control group and a complete medical history should be recruited in further studies. Using complementary methods to approve the PCR method can help further studies to demonstrate accurate results.